Materials with oxygen-regulated high-strength and tough self-lubricating coatings, preparation methods and applications
By adding nanoscale cuprous oxide to tin bronze, and using laser cladding and ultrasound-assisted technology to generate an alumina-strengthened copper composite coating, the problem of uneven distribution of ceramic particles during the laser cladding process is solved and high hardness is achieved , high wear resistance and friction-reducing coating performance improvement.
Patent Information
- Application Number
- CN202411210260.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-08-30
AI Technical Summary
The existing metal-based coatings are difficult to meet the performance requirements of high hardness, high wear resistance, high corrosion resistance in harsh environments. The difference in physical characteristics between ceramic materials and metal-based materials leads to uneven distribution of ceramic particles during laser cladding, which reduces the Coating properties.
On the basis of tin bronze, nanoscale cuprous oxide is added. Through the dilution effect of the laser cladding process, an alumina-reinforced copper composite coating with uniform particles and dispersed distribution is generated. Combined with the auxiliary control of the ultrasonic device, it ensures the uniformity of the alumina-reinforced phase. stable distribution.
It significantly improves the hardness, wear resistance and friction-reducing effect of the coating, extends the service life of the mechanical shaft, reduces preparation and maintenance costs, simplifies the process, and obtains better forming performance.
Smart Images

Figure CN118726972B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating preparation, and in particular to a material with an oxygen-regulated high-toughness self-lubricating coating, a preparation method and an application thereof. Background Art
[0002] Laser cladding is an emerging surface strengthening technology. Its principle is to use a high-density laser beam to reach an extremely high temperature instantly, melt the coating powder and the surface of the substrate to form a molten pool. As the laser moves, the molten pool quickly cools and solidifies to form a metal-based composite coating. Through the reasonable adjustment of materials and processes, a surface coating with specific functions such as high hardness, high wear resistance, high corrosion resistance, and high heat resistance can be obtained. Laser cladding for surface strengthening of workpieces has become a research hotspot in the field of surface engineering of mechanical parts.
[0003] With the increasingly harsh working environment, the commonly used metal-based coatings are gradually unable to meet the performance requirements. Compared with metal materials, ceramic materials are superior in hardness, toughness, wear resistance, corrosion resistance, etc. If ceramic-reinforced metal-based composite coatings can be prepared, the performance of the coating can be significantly improved. However, due to the large difference in the physical properties of ceramic materials and metal-based materials, directly adding ceramic particles will result in uneven distribution and easy agglomeration during the cladding process, which will lead to reduced performance and service life of the coating.
[0004] The demand for wear resistance of mechanical shaft materials is increasing. Copper alloy coatings have excellent thermal and electrical conductivity, but low hardness and strength, low wear resistance but good friction reduction effect. Copper alloys are suitable as solid lubricating materials to reduce friction coefficient and achieve friction reduction effect, but their wear resistance is poor, so it is necessary to develop a coating material with better performance. Summary of the invention
[0005] The purpose of the present invention is to provide a material with an oxygen-regulated high-strength and tough self-lubricating coating, as well as a preparation method and application. On the basis of tin bronze, the present invention adds nano-scale cuprous oxide, and based on a large number of powder ratios and preparation process tests, with the help of the dilution effect of the laser cladding process, the dilution rate that destroys the coating components becomes an advantage for improving the performance of the copper alloy coating, that is, a uniformly and dispersedly distributed alumina-reinforced copper composite coating is generated in the molten pool. The generated tin bronze coating is a good solid lubricating material that can reduce the friction coefficient of the coating; the generated alumina is an oxide ceramic strengthening phase with extremely high hardness and strength, which will increase the hardness and wear resistance of the coating. At the same time, the laser cladding of the present invention also utilizes the auxiliary regulation of an ultrasonic device, which can make the generated alumina reinforcement phase uniform and stable, and obtain a dispersion-reinforced copper alloy composite coating to meet the needs of actual use.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The first aspect of the present invention is to provide a method for preparing a material with an oxygen-regulated high-toughness self-lubricating coating, comprising the following steps:
[0008] Step (1) preparing coating powder; the coating powder comprises CuSn 12 Ni2 and Cu2O;
[0009] Step (2) uses laser cladding to prepare a coating on the surface of a substrate using coating powder under ultrasonic action, thereby obtaining a substrate-coating composite material, i.e., a material with an oxygen-regulated high-strength and tough self-lubricating coating; the substrate is an Al alloy.
[0010] Laser cladding is an advanced surface modification technology. It melts alloy powder or fuse material through laser beam irradiation and fuses it with the surface of the base material to form a new alloy layer. In this process, the base material will also melt due to absorption of laser energy to form a fusion zone. The ratio of this part of the base material to the molten metal of the cladding material is called the dilution rate; therefore, in the process of laser cladding, a part of the base element will inevitably diffuse into the coating prepared by laser cladding, thereby affecting the composition of the coating and causing the coating performance to decline. The present invention overcomes the disadvantages of the laser cladding dilution rate. Under the red-blue composite laser cladding, cuprous oxide decomposes oxygen at high temperature. With the help of the dilution effect of the laser cladding process, due to the high affinity between aluminum and oxygen, the molten pool spontaneously generates an alumina ceramic strengthening phase. The strengthening phase is dispersed and distributed with the assistance of ultrasonic vibration, thereby improving the hardness and wear resistance of the coating.
[0011] As a preferred implementation mode,
[0012] Step (1), the coating powder comprises 60% to 90% CuSn by mass fraction. 12 Ni2 and 10%~40%Cu2O.
[0013] As a preferred implementation mode,
[0014] Step (1), CuSn 12 The Ni2 powder and the Cu2O powder are ground evenly and then vacuum dried to obtain the coating powder.
[0015] As a preferred implementation mode,
[0016] The grinding is carried out by ball milling, wherein the mass ratio of ball to powder is 3:1-5:2; and / or,
[0017] The grinding speed is 300-500 rpm; and / or,
[0018] The grinding time is 120-240 min; and / or,
[0019] CuSn before grinding12 The particle size of Ni2 powder is 15-53 μm; and / or,
[0020] The particle size of the Cu2O powder before grinding is 10-50 nm; and / or,
[0021] The vacuum drying temperature is 120°C-180°C; and / or,
[0022] The vacuum drying time is 2-4 h.
[0023] As a preferred implementation mode,
[0024] The laser cladding in step (2) includes the following steps:
[0025] Step (a): fix the substrate surface in an ultrasonic device, and then set the laser head on the substrate surface to be clad;
[0026] Step (b): conveying coating powder to the surface of the substrate to be clad;
[0027] Step (c): The laser head emits a red-blue composite laser to the surface of the substrate to be clad and provided with coating powder, so as to prepare a coating on the surface of the substrate.
[0028] As a preferred implementation mode,
[0029] In step (a), the power of ultrasound is 500W-2000W; and / or,
[0030] The ultrasonic vibration frequency is 7kHZ-28kHZ; and / or,
[0031] The distance between the laser head and the substrate surface to be clad is 14mm-17mm; and / or,
[0032] The substrate is a preheated substrate, and the preheated substrate temperature is 500-600° C.; and / or,
[0033] Step (b), the powder feeding pressure of the coating powder is 0.2MPa-0.5MPa; and / or,
[0034] The coating powder feeding rate is 12g / min-24g / min; and / or,
[0035] Step (c), in the red and blue composite laser, the infrared laser power is 1200W-2200W; the blue laser power is 500W-800W; and / or, the wavelength of the blue laser is a laser beam of 420nm-450nm; the wavelength of the infrared laser is 720nm-820nm; and / or,
[0036] The scanning speed of the laser head is 20mm / s-50mm / s.
[0037] As a preferred implementation mode,
[0038] The Al alloy matrix is at least one of 6061 aluminum alloy, A356 aluminum alloy or ADC12 aluminum alloy.
[0039] A second aspect of the present invention is to provide a material with an oxygen-regulated high-strength and tough self-lubricating coating, wherein the coating of the material with an oxygen-regulated high-strength and tough self-lubricating coating contains aluminum oxide.
[0040] As a preferred implementation mode,
[0041] The hardness of the coating of the material with oxygen-regulated high-toughness self-lubricating coating is 496-885HV 0.5 ; preferably 525-735HV 0.5 ;
[0042] The friction coefficient is 0.17-0.56; preferably 0.17-0.38.
[0043] The third aspect of the present invention is to provide a material with an oxygen-regulated high-toughness self-lubricating coating prepared by the method described in the first aspect of the present invention or the material with an oxygen-regulated high-toughness self-lubricating coating as described in the second aspect of the present invention as a mechanical shaft material.
[0044] Compared with the existing copper alloy coating, the coating of the present invention enhances the surface hardness and wear resistance of the copper alloy coating. In actual production and life, by designing the comprehensive ratio of the mechanical shaft coating components, the service life of the shaft is effectively extended, the cost of preparing the copper alloy coating and the subsequent maintenance cost are reduced, the process is simplified, and better forming is obtained.
[0045] Advantages of the present invention:
[0046] In the process of preparing ceramic-reinforced metal-based composite coatings, most technologies directly mix ceramic particles and metal particles and then perform laser cladding. Due to the large difference in the physical properties of ceramic materials and metal-based materials, they will be unevenly distributed and easily agglomerated, which will lead to reduced performance and service life of the coating.
[0047] The CuSn selected by the present invention 12 Ni2 is used as the main powder with a small amount of Cu2O, CuSn 12Ni2 has excellent lubricity. Cu2O in the coating is used as an oxygen source, and Al alloy is used as a matrix. Due to the dilution effect during the laser cladding process, some Al elements enter the molten pool. Since the binding energy between O and Al is strong, the decomposed O and Al generate Al2O3 in situ inside the molten pool. The decomposed Cu will not cause impurity elements to mix in. Al2O3 is an oxide ceramic strengthening phase with extremely high hardness and strength. Therefore, the present invention uses a specific CuSn 12 The ratio of Ni2 and Cu2O, laser process parameters and ultrasonic power are rationally regulated to achieve uniform dispersion and conversion ratio of oxides, obtain a composite coating reinforced by dispersed hard particle phase and solid lubrication phase, and realize integrated friction reduction and wear resistance.
[0048] When laser cladding copper alloys, it is extremely difficult to laser clad copper alloy coatings because copper alloys have a reflectivity of more than 90% to infrared lasers. Higher power must be used, but higher power will increase the wear of the laser and make the molten pool unstable, forming cracks and pores, etc., resulting in poor coating quality. The absorption rate of copper alloys to blue lasers is more than ten times that of infrared lasers. A stable molten pool can be generated at a lower power, which reduces the dilution rate, powder splashing, pitting and other defects. By adjusting process parameters and using ultrasonic auxiliary devices, the oxide particles are evenly dispersed in the coating with the help of the cavitation effect, acoustic streaming effect, thermal effect and other effects of the physical field, so that the coating has the best strengthening effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a schematic diagram of the preparation process of the in-situ generated oxide self-lubricating coating of the present invention;
[0050] Figure 2 This is a macroscopic morphology of the coating prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0051] The present invention is further described in detail below through the accompanying drawings and specific embodiments.
[0052] Example 1
[0053] like Figure 1 The steps of the process diagram shown are for the preparation of the self-lubricating coating:
[0054] First, CuSn 12Ni2 powder (particle size 15-53μm, purity 99% spherical powder) and Cu2O powder (particle size 10-50nm, purity 99% irregular shape) are mixed. According to the ratio of each material scheme, a high-precision balance (accuracy: 0.001g) is used to weigh the mass of the required powder. Ceramic balls are placed in the ball mill according to the ball-to-powder mass ratio of 3:1, and the ball mill is sealed for ball milling. Set the ball mill parameters: speed 400rpm, and take out the ball milled powder after 200min. Finally, the ball-milled powder is placed in a vacuum drying oven and dried at 160℃ for 3 hours under a vacuum environment. After the powder is dried, the powder and ceramic balls are separated, and the dried powder is poured into the powder feeder.
[0055] The Al alloy substrate was polished by a grinding wheel using a fixture to remove the oxide layer on the surface. The substrate treated with anhydrous ethanol was preheated and placed in an ultrasonic device after preheating (the ultrasonic device is a metal plate with a groove that can vibrate ultrasonically, with a fixture inside, and the preheated substrate is embedded in the groove of the metal plate through the fixture). After setting the laser equipment and powder feeder equipment parameters, the ultrasonic device was turned on to achieve ultrasonic-assisted laser cladding for coating preparation; the laser cladding system adopted a red-blue laser cladding system equipped with a coaxial powder feeder, the wavelength of the blue fiber laser was 430nm, and the wavelength of the red laser was 760nm; the protective gas used an inert gas (argon, purity 99.999%) as the protective gas, and the protective gas flow rate was 8L / min. In order to further reduce the internal stress, the aluminum alloy substrate was preheated at a preheating temperature of 500℃. Use the card with the distance to adjust the distance between the substrate and the laser to 17mm, which can maintain the best orthogonal position where the laser and powder meet. Slightly tilt the laser head to prevent the laser from reflecting straight lines, so that the laser forms an angle of 85° with the substrate surface, and adjust the powder feeding pressure to the preset value (0.5MPa). First, pass the powder. After observing the powder outlet, change to external control on the powder feeder console, turn on the blue light water cooler, the red light water cooler, turn on the manual operation program, the spot diameter is 2mm, and the light waiting time is set to 2s (this step can ensure that after the powder reaches the surface of the substrate through the powder feeding tube, the red and blue lasers will emit light at the same time to prevent the forming quality before and after the coating is large. At the same time, turn on the ultrasonic device. After completing the above steps, start the program and prepare for the preparation of the composite coating). Test operation After confirming that the laser head is running correctly, change to the automatic operation program and wear goggles (to prevent blue light from causing irreversible damage to the eyes). During the cladding process, pay attention to the powder feeder and the laser system. If there is any abnormality, press the laser system emergency stop button immediately to prevent the laser from continuing to emit light.
[0056] In the present invention, under the action of ultrasound, laser cladding adopts powder feeder type laser cladding. The specific experimental process is as follows: start with setting parameters and procedures, first the powder is output for two seconds and then the red and blue lasers are output simultaneously. The powder is converted into a molten state by the laser energy before reaching the substrate. After reaching the substrate, the coating contacts the powder to achieve metallurgical bonding. The coating will not be shaken off by the slight vibration of ultrasound. With the help of the microscopic effect brought by the slight vibration assisted by ultrasound, the internal components of the coating will be dispersed and distributed, thereby improving the comprehensive performance of the coating.
[0057] Example 2
[0058] First, CuSn 12 Ni2 powder (particle size 15-53μm, purity 99% spherical powder) and Cu2O powder (particle size 10-50nm, purity 99% irregular shape) are mixed. According to the ratio of each material scheme, a high-precision balance (accuracy: 0.001g) is used to weigh the mass of the required powder. Ceramic balls are placed in the ball mill at a ball-to-powder mass ratio of 3:1, and the ball mill is sealed for ball milling. Set the ball mill parameters: speed 500rpm, and take out the ball-milled powder after 150min. Finally, the ball-milled powder is placed in a vacuum drying oven and dried at 120℃ for 4 hours under a vacuum environment. After the powder is dried, the powder and ceramic balls are separated, and the dried powder is poured into the powder feeder.
[0059] The Al alloy substrate was polished with a grinding wheel using a fixture to remove the oxide layer on the surface, and the substrate cleaned with anhydrous ethanol was placed in an ultrasonic device. The laser cladding system used a red-blue light laser cladding system equipped with a coaxial powder feeder. The wavelength of the blue fiber laser was 430 nm, and the wavelength of the red laser was 760 nm. Inert gas (argon, purity 99.999%) was used as the protective gas, and the protective gas flow rate was 8 L / min. In order to further reduce the internal stress, the aluminum alloy substrate was preheated at 600 °C. Use the card with the distance to adjust the distance between the substrate and the laser to 15mm, which can maintain the best orthogonal position where the laser and the powder meet. Slightly tilt the laser head to prevent the laser from reflecting straight lines, so that the laser forms an angle of 85° with the substrate surface, and adjust the powder feeding pressure to the preset value (0.5MPa). First, pass the powder. After observing the powder outlet, change to external control on the powder feeder console, turn on the blue light water cooler, the red light water cooler, turn on the manual operation program, the spot diameter is 2mm, and the light waiting time is set to 2s (this step can ensure that the red and blue lasers will emit light at the same time after the powder passes through the powder feeding tube to the surface of the substrate), to prevent the formation quality before and after the coating from being greatly different, and turn on the ultrasonic device at the same time. After completing the above steps, start the program and prepare for the preparation of the composite coating. After confirming that the laser head is running correctly, change to the automatic operation program and wear goggles (to prevent blue light from causing irreversible damage to the eyes). During the cladding process, pay attention to the powder feeder and the laser system. If there is any abnormality, press the laser system emergency stop button immediately to prevent the laser from continuing to emit light.
[0060] Example 3
[0061] First, CuSn 12 Ni2 powder (particle size 15-53μm, purity 99% spherical powder) and Cu2O powder (particle size 10-50nm, purity 99% irregular shape) are mixed. According to the ratio of each material scheme, a high-precision balance (accuracy: 0.001g) is used to weigh the mass of the required powder. Ceramic balls are placed in the ball mill according to the ball-to-powder mass ratio of 3:1, and the ball mill is sealed for ball milling. Set the ball mill parameters: speed 350rpm, and take out the ball milled powder after 165min. Finally, the ball-milled powder is placed in a vacuum drying oven and dried at 160℃ for 3 hours under a vacuum environment. After the powder is dried, the powder and ceramic balls are separated, and the dried powder is poured into the powder feeder.
[0062] The Al alloy substrate was polished with a grinding wheel using a fixture to remove the oxide layer on the surface, and the substrate cleaned with anhydrous ethanol was placed in an ultrasonic device. The laser cladding system used a red-blue light laser cladding system equipped with a coaxial powder feeder. The wavelength of the blue fiber laser was 430 nm, and the wavelength of the red laser was 760 nm. Inert gas (argon, purity 99.999%) was used as the protective gas, and the protective gas flow rate was 8 L / min. In order to further reduce the internal stress, the aluminum alloy substrate was preheated at 600 °C. Use the card with the distance to adjust the distance between the substrate and the laser to 16mm, which can maintain the best orthogonal position where the laser and the powder meet. Slightly tilt the laser head to prevent the laser from reflecting straight lines, so that the laser forms an angle of 85° with the substrate surface, and adjust the powder feeding pressure to the preset value (0.4MPa). First, pass the powder. After observing the powder outlet, change to external control on the powder feeder console, turn on the blue light water cooler, the red light water cooler, turn on the manual operation program, the spot diameter is 2mm, and the light waiting time is set to 2s (this step can ensure that the red and blue lasers emit light at the same time after the powder passes through the powder feeding tube to the surface of the substrate), to prevent the formation quality before and after the coating from being greatly different, and turn on the ultrasonic device at the same time. After completing the above steps, start the program and prepare for the preparation of the composite coating. After confirming that the laser head is running correctly, change to the automatic operation program and wear goggles (to prevent blue light from causing irreversible damage to the eyes). During the cladding process, pay attention to the powder feeder and the laser system. If there is any abnormality, press the laser system emergency stop button immediately to prevent the laser from continuing to emit light.
[0063] Figure 2 This is a macroscopic morphology of the coating prepared in Example 3 of the present invention; Figure 2 It can be seen that the coating prepared by the present invention forms a continuous, dense, crack-free and pore-free copper alloy cladding layer.
[0064] Example 4
[0065] First, CuSn 12 Ni2 powder (particle size 15-53μm, purity 99% spherical powder) and Cu2O powder (particle size 10-50nm, purity 99% irregular shape) are mixed. According to the ratio of each material scheme, a high-precision balance (accuracy: 0.001g) is used to weigh the mass of the required powder. Ceramic balls are placed in the ball mill according to the ball-to-powder mass ratio of 4:2, and the ball mill is sealed for ball milling. Set the ball mill parameters: speed 450rpm, and take out the ball milled powder after 135min. Finally, the ball-milled powder is placed in a vacuum drying oven and dried at 180℃ for 2h under a vacuum environment. After the powder is dried, the powder and ceramic balls are separated, and the dried powder is poured into the powder feeder.
[0066] The Al alloy substrate was polished with a grinding wheel using a fixture to remove the oxide layer on the surface, and the substrate cleaned with anhydrous ethanol was placed in an ultrasonic device. The laser cladding system used a red-blue light laser cladding system equipped with a coaxial powder feeder. The wavelength of the blue fiber laser was 430 nm, and the wavelength of the red laser was 760 nm. Inert gas (argon, purity 99.999%) was used as the protective gas, and the protective gas flow rate was 8 L / min. In order to further reduce the internal stress, the aluminum alloy substrate was preheated at 600 °C. Use the card with the distance to adjust the distance between the substrate and the laser to 16mm, which can maintain the best orthogonal position where the laser and the powder meet. Slightly tilt the laser head to prevent the laser from reflecting straight lines, so that the laser forms an angle of 85° with the substrate surface, and adjust the powder feeding pressure to the preset value (0.4MPa). First, pass the powder. After observing the powder outlet, change to external control on the powder feeder console, turn on the blue light water cooler, the red light water cooler, turn on the manual operation program, the spot diameter is 2mm, and the light waiting time is set to 2s (this step can ensure that after the powder reaches the surface of the substrate through the powder feeding tube, the red and blue lasers will emit light at the same time to prevent the forming quality before and after the coating is greatly different. At the same time, turn on the ultrasonic device, start the program after completing the above steps, and prepare for the preparation of the composite coating. After confirming that the laser head is running correctly, change to the automatic operation program and wear goggles (to prevent blue light from causing irreversible damage to the eyes). During the cladding process, pay attention to the powder feeder and the laser system. If there is any abnormality, press the laser system emergency stop button immediately to prevent the laser from continuing to emit light.
[0067] Example 5
[0068] First, CuSn 12 Ni2 powder (particle size 15-53μm, purity 99% spherical powder) and Cu2O powder (particle size 10-50nm, purity 99% irregular shape) are mixed. According to the ratio of each material scheme, a high-precision balance (accuracy: 0.001g) is used to weigh the mass of the required powder. Ceramic balls are placed in the ball mill according to the ball-to-powder mass ratio of 5:2, and the ball mill is sealed for ball milling. Set the ball mill parameters: speed 300rpm, and take out the ball milled powder after 240min. Finally, the ball-milled powder is placed in a vacuum drying oven and dried at 180℃ for 2h under a vacuum environment. After the powder is dried, the powder and ceramic balls are separated, and the dried powder is poured into the powder feeder.
[0069] The Al alloy substrate was polished with a grinding wheel using a fixture to remove the oxide layer on the surface, and the substrate cleaned with anhydrous ethanol was placed in an ultrasonic device. The laser cladding system used a red-blue light laser cladding system equipped with a coaxial powder feeder. The wavelength of the blue fiber laser was 430 nm, and the wavelength of the red laser was 760 nm. Inert gas (argon, purity 99.999%) was used as the protective gas, and the protective gas flow rate was 8 L / min. In order to further reduce the internal stress, the aluminum alloy substrate was preheated at 600 °C. Use the card with the distance to adjust the distance between the substrate and the laser to 16mm, which can maintain the best orthogonal position where the laser and the powder meet. Slightly tilt the laser head to prevent the laser from reflecting straight lines, so that the laser forms an angle of 85° with the substrate surface, and adjust the powder feeding pressure to the preset value (0.3MPa). First, pass the powder. After observing the powder outlet, change to external control on the powder feeder console, turn on the blue light water cooler, the red light water cooler, turn on the manual operation program, the spot diameter is 2mm, and the light waiting time is set to 2s (this step can ensure that the red and blue lasers will emit light at the same time after the powder passes through the powder feeding tube to the surface of the substrate), to prevent the formation quality before and after the coating from being greatly different, and turn on the ultrasonic device at the same time. After completing the above steps, start the program and prepare for the preparation of the composite coating. After confirming that the laser head is running correctly, change to the automatic operation program and wear goggles (to prevent blue light from causing irreversible damage to the eyes). During the cladding process, pay attention to the powder feeder and the laser system. If there is any abnormality, press the laser system emergency stop button immediately to prevent the laser from continuing to emit light.
[0070] Other process parameters of the above embodiments 1-5 of the present invention are shown in Table 1.
[0071] Table 1 Other process parameters of Examples 1-5
[0072]
[0073] The optimal overlap rate of the above embodiment of the present invention is 80-85%. The overlap rate is an important parameter affecting the roughness of the cladding surface, which shows that the above laser cladding method can effectively and fully melt the material and reduce the internal stress.
[0074] Comparative Example 1
[0075] It adopts a preparation method that is basically the same as that of Example 1, the only difference being that it does not use ultrasonic assistance, but only performs laser cladding.
[0076] Comparative Example 2
[0077] The preparation method is basically the same as that of Example 1, except that, by mass fraction, the coating powder includes 50% CuSn 12 Ni2 and 50% Cu2O.
[0078] Comparative Example 3
[0079] The preparation method is basically the same as that of Example 1, with the only difference being that only infrared laser is used for laser cladding.
[0080] Comparative Example 4
[0081] The preparation method is basically the same as that of Example 1, with the only difference being that the Al alloy substrate of Example 1 is replaced by a pure aluminum substrate.
[0082] Test method:
[0083] The samples were cut into Specifications, cleaned with ultrasonic cleaning machine, mounted with acrylic plastic glue, polished with 400 mesh, 600 mesh, 800 mesh, 1200 mesh, 1500 mesh, 2000 mesh sandpaper, and polished to mirror finish with diamond polishing agent on polishing machine.
[0084] The wear resistance test of the cladding layer was carried out on a friction and wear machine. The longitudinal load was 100g, the reciprocating speed was 3Hz, the stroke was 4mm, and the test time was 30min. The depth and width of the wear scar were measured and metallographic observation was carried out.
[0085] Carry out hardness test at different positions of coating on hardness tester, with vertical load of 500g, action time of 10s, and positions from coating-bonding surface-substrate, 5 points horizontally and 10 points vertically, and record the average hardness.
[0086] The coating properties of the above embodiments of the present invention and the comparative examples are shown in Table 2.
[0087] Table 2
[0088]
[0089] Note: In the present invention, the higher the hardness, the more wear-resistant it is; the smaller the friction coefficient, the more wear-reducing it is.
[0090] Table 2 shows the properties of coatings prepared by different processes and different powder ratios. It can be seen that the formation of moderate alumina ceramic reinforcement phase slightly increases the friction reduction of the coating, while the hardness increases significantly, but excessive formation will lead to a serious decrease in the friction reduction effect and hardness, destroying the coating performance.
[0091] By comparing the results of Example 1 with Comparative Example 1, it can be seen that the laser cladding process of Comparative Example 1 does not have the auxiliary effect of ultrasound, and the obtained coating has poor molding quality. The reason is that the lack of the acoustic streaming effect brought by ultrasonic vibration makes the reinforcement phase formed inside the molten pool unevenly distributed, the grains are coarse, and the hardness is lower and the friction coefficient is larger. This shows that its hardness, wear resistance and wear reduction effect are not as good as the coating prepared in Example 1 of the present invention.
[0092] By comparing the results of Example 1 with those of Comparative Example 2, it can be seen that during the laser cladding process of Comparative Example 2, the proportion of O in the molten pool is increased, and the hardness of the resulting coating is slightly higher. The reason is that more aluminum oxide reinforcement items are generated but they are not uniform, and this leads to an increase in the friction coefficient, indicating that its comprehensive performance and wear reduction effect are not as good as the coating prepared in Example 1 of the present invention.
[0093] By comparing the results of Example 1 with those of Comparative Example 3, it can be seen that the laser cladding process of Comparative Example 3 does not have the auxiliary effect of blue light, and the hardness of the obtained coating is very low. The reason is that a large amount of energy is directly concentrated on the substrate and is not absorbed by the copper alloy powder, resulting in an extremely unstable molten pool. The quality of the generated coating is very poor, indicating that its comprehensive performance is far inferior to the coating prepared in Example 1 of the present invention.
[0094] By comparing the results of Example 1 with those of Comparative Example 4, it can be seen that the substrate of the laser cladding process of Comparative Example 4 is a pure aluminum substrate, which results in a relatively high dilution rate of the Al element and an excessively large proportion of the Al element in the coating. The hardness of the resulting coating is relatively high because more aluminum oxide reinforcement phase is generated, which also leads to an increase in the friction coefficient, indicating that its overall performance is lower than that of the coating prepared in Example 1 of the invention.
[0095] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a material with an oxygen-regulated high-toughness self-lubricating coating, characterized in that: The following steps are involved: Step (1) preparing coating powder; the coating powder comprises CuSn 12 Ni2 and Cu2O; wherein, by mass fraction, the coating powder comprises 80% CuSn 12 Ni2 and 20% Cu2O; Step (2) using laser cladding to prepare a coating on the surface of a substrate using coating powder under ultrasonic action, thereby obtaining a material with an oxygen-regulated high-strength and tough self-lubricating coating; the substrate is an Al alloy; The laser cladding in step (2) includes the following steps: Step (a): fix the substrate surface in an ultrasonic device, and then set the laser head on the substrate surface to be clad; Step (b): conveying coating powder to the surface of the substrate to be clad; Step (c): a laser head emits a red-blue composite laser to the surface of the substrate to be clad and provided with coating powder, so as to prepare a coating on the surface of the substrate; In step (a), the power of ultrasound is 500W-2000W; The vibration frequency of ultrasound is 7kHZ-28kHZ; Step (a), Use the card with the distance made to adjust the distance between the substrate and the laser at the intersection to 16mm; The substrate is a preheated substrate, and the temperature of the preheated substrate is 600° C. Step (b), conveying the coating powder at a powder feeding pressure of 0.4 MPa; The powder feeding rate of the coating powder is 1.2g / min; Step (c), in the red and blue composite laser, the infrared laser power is 1500W; the blue laser power is 500W; The wavelength of blue laser is 430nm; the wavelength of infrared laser is 760nm; The scanning speed of the laser head is 30 mm / s; The coating of the material with oxygen-regulated high-toughness self-lubricating coating contains aluminum oxide.
2. The method for preparing a material with an oxygen-regulated high-toughness self-lubricating coating according to claim 1, characterized in that: Step (1), CuSn 12 The Ni2 powder and the Cu2O powder are ground evenly and then vacuum dried to obtain the coating powder.
3. The method for preparing a material with an oxygen-regulated high-toughness self-lubricating coating according to claim 2, characterized in that: The grinding is carried out by ball milling, wherein the mass ratio of ball to powder is 3:1-5:2; and / or, The grinding speed is 300-500 rpm; and / or, The grinding time is 120-240 min; and / or, CuSn before grinding 12 The particle size of Ni2 powder is 15-53 μm; and / or, The particle size of the Cu2O powder before grinding is 10-50 nm; and / or, The vacuum drying temperature is 120°C-180°C; and / or, The vacuum drying time is 2-4 h.
4. The method for preparing a material with an oxygen-regulated high-toughness self-lubricating coating according to claim 1, characterized in that: The Al alloy matrix is at least one of 6061 aluminum alloy, A356 aluminum alloy or ADC12 aluminum alloy.
Citation Information
Patent Citations
Method for producing sliding layer of sliding bearing using alloy and / or material
CN114930040A
Process for cladding tin bronze alloy powder by blue and red laser compounding
CN115821251A